Antimicrobial, mechanical and barrier properties of triticale protein films incorporated with oregano essential oil - Aguirre, Alicia del Valle (2013)
Antimicrobial triticale protein films were prepared by incorporating oregano essential oil (OEO). The effect of different concentrations of OEO on antimicrobial activity and on mechanical and barrier properties of films plasticized with glycerol was evaluated and compared with control films (without antimicrobial agent). The addition of OEO did not affect the water vapor permeability of films, increased water solubility and the percent elongation of the films, and reduced tensile strength and Young's modulus. Films with OEO showed higher antimicrobial activity against the Gram positive bacterium Staphylococcus aureus, and lower for Gram negative (Escherichia coli and Pseudomonas aeruginosa). The obtained results proved the permanence of OEO in the polymer matrix after processing, making them able to be used as active additives in film formulation. © 2013 Elsevier Ltd. All rights reserved.